Analisis Pengaruh Kualitas Layanan Internet Banking terhadap Kepuasan dan Loyalitas Nasabah dengan Menggunakan E-S-Qual dan E-Recs-Qual (Studi pada Pengguna Layanan BSMNet Bank Syariah Mandiri) - Ali Arifin; Ari Kusyanti; Yusi Tyroni Mursityo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Bank Syariah Mandiri (BSM) is one of the example bank which applied the internet banking technology as the additional service to increase customers’ experience in online transaction via internet, which through BSMNet service. The application of BSMNet is one of BSM’s commitment form in order to give a better service, and next it could be felt and evaluated by the customers who has used it. This evaluation could affect the satisfaction level of customers. To measure customers’ satisfaction, it needs a precise tool, using E-S-Qual and E-Resc-Qual method for example. From this problem, the researcher do the test toward the effect of internet banking service quality which offered by BSM to know customers’ satisfaction and also the customers’ loyalty. This test is using E-S-Qual and E-Resc-Qual method with linear regression analytics. The researcher used Bank Syariah Mandiri’s customers in Cilacap area who used BSMNet Internet banking as the respondent sample. The result of this test shows that customers’ satisfaction is significantly affected by all of the variables of E-S-Qual and E-Resc-Qual (efficiency, fulfillment, system availability, privacy, responsiveness, compensation, contact), meanwhile customers’ satisfaction is partially affected by fulfillment and efficiency. The effect of this satisfaction will affect the customers’ loyalty of using BSMNet internet banking service.